FAKTOR-FAKTOR YANG MEMENGARUHI MINAT PEMUDA PEDESAAN DALAM MELANJUTKAN USAHATANI PADI DI KABUPATEN LAMPUNG TENGAH - Alvita Raissa Marza; R Hanung Ismono; Eka Kasymir (Lampung University, 2020)
This research aims to analyze the income of rice farming, the factors affecting of rural youth interest to continue rice farming, pull and push factors to work in agriculture sector. This research was purposively conducted in Trimurjo Sub District and Seputih Banyak Sub District, Central Lampung Regency from Marchto April 2018. There are 63 respondents taken by using proportional random sampling. The data of this research are collected by using survey method. The research data was analyzed bydescriptive qualitativeand quantitative. The descriptive qualitative and quantitative analysis was used to analyze farm income, binary logistic regression, and Spearman test. The results of this research show that the income of rice farming is Rp15.181.983,23 in the first planting season and Rp16.931.595,67 in the second planting season. Factors affecting of youth interest to continue rice farming are land area, age, education level, distance of youth residence to the city center. The pull factors to work in agriculture sector are the income of rice farming and availability of land area. The push factors to work in agriculture sector are limited employment opportunities, low level of education and too much free time.Key words: farm, interest, pull factor, push factor, youth